2016
DOI: 10.1097/dbp.0000000000000321
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and Acculturation Stress: A Longitudinal Study of Children's Well-Being from Prenatal Development to 5 Years of Age

Abstract: Objective To examine whether cumulative family discrimination and acculturation stress (prenatally to 24-months postpartum) among Mexican-origin adolescent mothers and their mother-figures predicted children’s socio-emotional functioning and academic achievement at 5 years of age, and the role of maternal depressive symptoms and mother-child interactions in the association. Methods Mexican-origin families (N = 204) with an adolescent mother, a child, and a mother-figure participated in a 6-wave longitudinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 50 publications
5
41
1
Order By: Relevance
“…12 Another study found that among Mexican-origin families, cumulative discrimination experienced by adolescent mothers/mother figures from pregnancy through 24 months postpartum predicted poorer social-emotional development and academic achievement in children at 5 years. 21 A daily diary study with Mexican immigrant parents of 3 to 5 year old children also found that on days that parents experienced greater discrimination at the workplace, they reported more externalizing and internalizing behaviors as well as less positive behaviors in their children. 22 These findings support that there are intergenerational consequences of discrimination beyond birth outcomes.…”
Section: The Role Of Discriminationmentioning
confidence: 98%
“…12 Another study found that among Mexican-origin families, cumulative discrimination experienced by adolescent mothers/mother figures from pregnancy through 24 months postpartum predicted poorer social-emotional development and academic achievement in children at 5 years. 21 A daily diary study with Mexican immigrant parents of 3 to 5 year old children also found that on days that parents experienced greater discrimination at the workplace, they reported more externalizing and internalizing behaviors as well as less positive behaviors in their children. 22 These findings support that there are intergenerational consequences of discrimination beyond birth outcomes.…”
Section: The Role Of Discriminationmentioning
confidence: 98%
“…Culture-specific stressors (e.g., discrimination, stressful life events, and acculturative stress) have predicted parental depression [36,37] and provide key sociocultural contexts in which to examine maternal and child health [38]. Acculturative stress, stemming from psychosocial adjustment to a host culture, may affect both immigrants and later generations who have simultaneously assimilated to a new culture and maintained cultural heritage [39].…”
Section: Plos Onementioning
confidence: 99%
“…Specific to adolescent mothers, this may mean that prevention programs, which typically focus on supporting adolescent mothers' parenting processes (e.g., Easterbrooks, Kotake, Raskin, & Bumgamer, 2016;Jacobs et al, 2016), should also consider adolescent mothers' experiences that are not solely tied to their parenting status. Growing evidence suggests that parents' discrimination experiences impact parent-child interactions and children's developmental outcomes (Zeiders, Umaña-Taylor, Jahromi, Updegraff, & White, 2016). Thus, practitioners and family members should be aware that experiences of discrimination can pose significant risks to adolescent mothers, their ERI development, their parenting, and ultimately their young children's development.…”
Section: Contributions Limitations and Future Directionsmentioning
confidence: 99%